1997
DOI: 10.1177/10454411970080010101
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Control of Early Tooth Development

Abstract: Most vertebrate organs begin their initial formation by a common, developmentally conserved pattern of inductive tissue interactions between two tissues. The developing tooth germ is a prototype for such inductive tissue interactions and provides a powerful experimental system for elucidation of the genetic pathways involved in organogenesis. Members Msxl is required for the transmission of Bmp4 expression from dental epithelium to mesenchyme and also for Lefi expression.In addition, we consider the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
153
0
6

Year Published

1998
1998
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(161 citation statements)
references
References 258 publications
2
153
0
6
Order By: Relevance
“…Numerous reports have suggested that apoptosis is associated with down-or upregulation of various developmental regulatory genes (Wyllie, 1987;Buttyan et al, 1988;Collins et al, 1994;Maas and Bei, 1997;Kerä nen et al, 1999). Some evidence even suggests that all cells undergo apoptosis by default unless they are rescued by survival factors (Raff, 1992;Steller, 1995).…”
Section: Spatiotemporal Distribution Of Apoptosis In Cloacal Developmentmentioning
confidence: 99%
“…Numerous reports have suggested that apoptosis is associated with down-or upregulation of various developmental regulatory genes (Wyllie, 1987;Buttyan et al, 1988;Collins et al, 1994;Maas and Bei, 1997;Kerä nen et al, 1999). Some evidence even suggests that all cells undergo apoptosis by default unless they are rescued by survival factors (Raff, 1992;Steller, 1995).…”
Section: Spatiotemporal Distribution Of Apoptosis In Cloacal Developmentmentioning
confidence: 99%
“…Signaling from the mesenchyme is required for further tooth morphogenesis. Several secreted signaling molecules (Bmp2,Bmp4,Fgf4,Fgf8,and Shh) and transcription factors (Lef1,Msx1,Msx2,Pitx2,and Pax9) have been shown to play important roles in these processes (Maas and Bei, 1997;Neubü ser et al, 1997;Hardcastle et al, 1998;Thesleff and Mikkola, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The functional differentiation of ameloblasts is initiated 24 hr later. Signaling molecules, which belong to several distinct families including BMPs, FGFs, and WNTs, control each of these steps (for review see Maas and Bei 1997;Tucker and Sharpe 1999;Thesleff and Mikkola 2002).…”
mentioning
confidence: 99%